Three-Dimensional Renal Organoids from Whole Kidney Cells: Generation, Optimization, and Potential Application in Nephrotoxicology In Vitro. (11th March 2020) - Ding, Beichen; Sun, Guoliang; Liu, Shiliang; Peng, Ejun; Wan, Meimei; Chen, Liang; Jackson, John; Atala, Anthony
The kidney function of patients with chronic kidney disease (CKD) is impaired irreversibly. Organ transplantation is the only treatment to restore kidney function in CKD patients. The assessment of new potential therapeutic procedures relies heavily on experimental animal models, but it is limited by its human predictive capacity. In addition, the frequently used two-dimensional in vitro human renal cell models cannot replicate all the features of the in vivo situation. In this study, we developed a three-dimensional (3D) in vitro human renal organoid model from whole kidney cells as a promising drug screening tool. At present, the renal tissue generated from human pluripotent stem cells (hPSCs) exhibits intrinsic tumorigenicity properties. Here we first developed a 3D renal organoid culture system that originated from adult differentiated cells without gene modification. Renal organoids composed of multiple cell types were created under optimal experimental conditions and evaluated for morphology, viability and erythropoietin production. As a novel screening tool for renal toxicity, 3D organoids were exposed to three widely used drugs: aspirin, penicillin G and cisplatin. The study results showed this 3D renal organoid model can be used as a drug screening tool, a new in vitro 3D human kidney model, and provide hope for potential regenerative therapies for CKD.